Human β-Defensin 2 as a Novel Diagnostic Marker of Iraqi Patients with Rheumatoid Arthritis - Farhan, Layla O.; Khaleel, Fayhaa M.; Taha, Ekhlass M. (Iraqi Journal of Science, 2023)
Rheumatoid arthritis (RA) is an autoimmune disorder of the joints that is characterized by extra-articular involvement in addition to inflammatory arthritis. Joint and periarticular tissue loss brought on by inflammation results in functional impairment. To lessen the significant daily challenges that patients confront and to ensure better outcomes, early detection and treatment are essential. The study's objective was to establish the use of human β-defensin-2 (HBD-2) as a RA diagnostic marker. A total of 60 RA patients and 30 healthy controls participated in the research. The ELISA technique was used to measure serum HBD-2. The following tests were performed: complete blood count (CBC), erythrocyte sedimentation rate (ESR), renal function test, and liver function test. In comparison to the healthy control group, the RA group exhibited a substantially higher blood HBD-2 levels (p ≤0.001). Additionally, there was no significant association between serum HBD-2 and urea, creatinine, AST, ALT, and ESR (P>0.05). When RA was distinguished from the group of healthy individuals, the area under the curve (AUC) demonstrated excellent diagnostic accuracy (AUC = 0.990, p = 0.001). (0.9667). As a result, serum HBD-2 may be used as a reliable RA diagnostic marker.